(untitled) (Medico Legal Update, 2019)
Objectives: In this study, we aimed to evaluate the validity and reliability of the scale for dental hygienists’ role as knowledge broker, a tool potentially useful to help to develop dental hygienists’ role as a knowledge broker that meet the needs of the field and include it in dental hygiene curricula. Method: This manuscript reports on a complex descriptive study involving both qualitative and quantitative sub-studies. It also includes a methodological study aiming to develop and verify the content validity and reliability of a scale for dental hygienists’ role as a knowledge broker. The survey questionnaire was distributed to 240 dental hygienists who currently work in care institutions, including private hospital, dental hospital, or general hospital for at least three months, between June 8, 2015 and July 13, 2015. Findings: To verify the reliability, validity, and unidimensionality of the 40 questionnaire items, exploratory factor analysis was performed with Varimax rotation. The exploratory factor analysis led to 17 items for three factors. In the confirmatory factor analysis, the path coefficients for all items were significant, at .588-.857.Based on the results of exploratory and confirmatory factor analyses and literature review of the role of knowledge brokers, its subfactors 1, 2, and 3 were named “explain and promote understanding”, “deliver knowledge”, and “link to resources”, respectively. The goodness of fit of the structural equation model was examined using the following indices: =3.066, GFI=.860, AGFI= .805, TLI=.882, CFI=.904, RMSEA=.094 Applications: We developed and validated a scale to assess the roles of dental hygienists in Korea as a knowledge broker. Reflecting the newly demanded roles of knowledge brokers in educational curricula will surely help dental hygienists to advance and improve themselves as health professionals.